A review of studies looking at quality of life and psychological impact in people with photodermatoses – skin diseases triggered by sunlight. (2nd May 2020) - Rutter, K.J.; Ashraf, I.; Cordingley, L.; Rhodes, L.E.
Summary: Photodermatoses, or photosensitivity conditions, are a group of skin disorders caused by exposure to sunlight, overall affecting a large number of people. They cause a range of distressing symptoms including pain and burn, and can make the skin blister, flake and scar. The conditions themselves and the need for patients to avoid and protect themselves from sunlight may affect quality of life and psychological health. This study, from the U.K., aimed to find out what methods of assessment (tools) have been used to evaluate quality of life and psychological health in photodermatoses, and report what the impact is for patients. The authors reviewed relevant published English‐language studies and summarised their findings. 20 studies were included: 19 assessing quality of life and three assessing psychological function. Six different tools had been used to assess quality of life, and four different tools to assess psychological health. It was shown that 31‐39% of patients with photodermatoses experienced a very large impact on their quality of life. There was a particular impact on issues related to employment, social/leisure activities and clothing choices. Patients had around double the rates of anxiety and depression found in the general population, although few studies focussed on psychological health. The authors also noted that most available tools were not designed to address the unique impact of intermittent sunlight‐induced skin conditions and suggested that development of more specific tools could be beneficial. In conclusion, this study confirmed that patients with photodermatoses experience substantial impact on their quality of life and that more research is needed. This is a summary of the study: Quality of life and psychological impact in the photodermatoses: a systematic review. Abstract : Linked Article:  Rutter et al. Br J Dermatol 2020; 182 :1092–1102